Nursing Care for Clients with Disorders Altered Sensory Perception Hallucinations Hearing - Nurlela, Lela; Hastutiningtyas, Wahidyanti Rahayu; Hamdanesti, Rischa; Ervan, Ervan; Makualaina, Fenska Narly; Nurhaedah, Nurhaedah (International Journal of Health Sciences, 2024)
Hallucinations are perceptual disorders where the patient perceives something that is not actually happening. An application of the five senses without any external stimulation. An appreciation experienced by a perception through the five senses without external stimulus: False perception. In contrast to illusions where the patient experiences a wrong perception of the stimulus, misperceptions in hallucinations occur without any external stimulus occurring. Internal stimuli are perceived as something that actually exists by the patient. The aim of this research is to gain real experience in providing nursing care to patients with auditory hallucinations, it is hoped that they will be able to identify all problems that occur in connection with hallucinations. The methods used in writing this paper are the library method, interview method and observation method. The results of the research showed that the nursing problems found were in the case of patients with auditory hallucinations based on the theory that there were three nursing diagnoses, namely: Risk of harm to self, others and the environment related to auditory hallucinations; Changes in sensory perception: auditory hallucinations related to withdrawal; Impaired social interactions: Withdrawal is associated with low self-esteem. The conclusion is that hallucinations often occur in schizophrenia patients with nursing problems of low self-esteem and/or withdrawal.